2000
DOI: 10.1074/jbc.275.12.8785
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, Post-translation Modification, and Functional Characterization of Drm/Gremlin

Abstract: Down-regulated by mos (Drm)/Gremlin is a highly conserved protein whose properties and expression pattern suggest a role in early development, tissue-specific differentiation, and cell transformation. We have investigated the biosynthesis and processing of Drm expressed endogenously in rat fibroblasts or overexpressed following transient or stable transfection. Analysis of metabolically labeled cells revealed that Drm exists in secreted and cell-associated forms that exhibit similar mobilities in SDS-polyacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 134 publications
(126 citation statements)
references
References 35 publications
4
119
0
3
Order By: Relevance
“…BMP-4 with relatively high affinity, which gives further credence to our hypothesis that gremlin inhibits BMP-4 signaling in SP-C/gremlin mice (Topol et al, 2000). Interestingly, BMP-4 has been shown to regulate proximal-distal patterning during tooth development, suggesting that this regulatory role for BMP-4 may be generalized to tissues other than lung (Tucker et al, 1998;Cheifetz, 1999).…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…BMP-4 with relatively high affinity, which gives further credence to our hypothesis that gremlin inhibits BMP-4 signaling in SP-C/gremlin mice (Topol et al, 2000). Interestingly, BMP-4 has been shown to regulate proximal-distal patterning during tooth development, suggesting that this regulatory role for BMP-4 may be generalized to tissues other than lung (Tucker et al, 1998;Cheifetz, 1999).…”
Section: Discussionsupporting
confidence: 48%
“…One important difference between the studies presented here and those reported by Weaver et al is that endogenous gremlin is expressed in the proximal airway epithelium, whereas mouse noggin is normally expressed in the distal mesenchyme of the embryonic lung (Weaver et al, 1999). These data, along with previous reports that gremlin inhibits signaling by BMP-4, strongly implicate gremlin as an important regulator of proximal-distal patterning during lung development and suggests that gremlin may program proximal lung epithelial cell fate through inhibition of BMP signaling (Hsu et al, 1998;Topol et al, 2000).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations